Ð¡Ñ€Ð°Ð²Ð½Ð¸Ñ‚ÐµÐ»ÑŒÐ½Ð¾Ðµ Ð¸ÑÑÐ»ÐµÐ´Ð¾Ð²Ð°Ð½Ð¸Ðµ Ñ‡ÑƒÐ²ÑÑ‚Ð²Ð¸Ñ‚ÐµÐ»ÑŒÐ½Ð¾ÑÑ‚Ð¸ Ð¿Ñ€ÐµÐ´Ð²Ð°Ñ€Ð¸Ñ‚ÐµÐ»ÑŒÐ½Ð¾ Ð¾Ð±ÐµÐ·Ð²Ð¾Ð¶ÐµÐ½Ð½Ñ‹Ñ… ÑÑ€Ð¸Ñ‚Ñ€Ð¾Ñ†Ð¸Ñ‚Ð¾Ð² Ñ‡ÐµÐ»Ð¾Ð²ÐµÐºÐ° Ð¸ Ð±Ñ‹ÐºÐ° Ðº Ð³Ð¸Ð¿ÐµÑ€Ñ‚Ð¾Ð½Ð¸Ñ‡ÐµÑÐºÐ¾Ð¼Ñƒ ÑÑ‚Ñ€ÐµÑÑÑƒ - Aleksandrova, D. I.; Orlova, N. V.; Shpakova, N. M. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2007)
Preliminary incubation of human and bovine erythrocytes in 0.4 and 1.0 M NaCl, correspondingly, results in the formation of a resistant cell state to the following 4.0 M NaCl effect. Maximum erythrocyte shrinking at the stage of preliminary incubation in moderately hypertonic media was shown as correlating with the minimum hemolysis level under cell transfer into 4.0 M NaCl-containing medium. At 37°C the level of minimum hypertonic hemolysis and minimum hematocrit value for bovine erythrocytes is lower that the similar ones, obtained for human erythrocytes. The reduction of experimental temperature down to 0°C results in hemolysis level and human erythrocyte volume decrease compared to 37°C.